Social Experimentation, Program Evaluation, and Public Policy 2008
DOI: 10.1002/9781444307399.ch24
|View full text |Cite
|
Sign up to set email alerts
|

An Effectiveness‐Based Evaluation of Five State Pre‐Kindergarten Programs

Abstract: Since 1980, the number of state pre-kindergarten (pre-K)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 0 publications
0
61
1
Order By: Relevance
“…The results of a five-state study of prekindergarten programs in Michigan, New Jersey, Oklahoma, South Carolina, and West Virginia are generally consistent with those of the programs in Tulsa and Boston [12]. The five-state study found generally positive effects on children's development, although the effects varied somewhat by state and outcome, with the largest and most consistent effects across states found for a measure of children's pre-reading skills (print awareness).…”
Section: Programs Improve School Readiness Especially For the Disadvmentioning
confidence: 53%
“…The results of a five-state study of prekindergarten programs in Michigan, New Jersey, Oklahoma, South Carolina, and West Virginia are generally consistent with those of the programs in Tulsa and Boston [12]. The five-state study found generally positive effects on children's development, although the effects varied somewhat by state and outcome, with the largest and most consistent effects across states found for a measure of children's pre-reading skills (print awareness).…”
Section: Programs Improve School Readiness Especially For the Disadvmentioning
confidence: 53%
“…Gormley et al (2010 find that the average effect size of Tulsa pre-K on literacy and math tests is over 70 percent greater than the effect size for Tulsa Head Start. Wong et al (2008) argue that their average results from five states for various tests are about twice the average short-run effect sizes of Head Start in the recent experiment. This may exaggerate Head Start's problems, as a greater portion of the Head Start control group will enroll in an alternative pre-K program.…”
Section: Notesmentioning
confidence: 99%
“…Such studies have been done in many states, including New Jersey, Michigan, West Virginia, South Carolina, Oklahoma, New Mexico, and Tennessee, and in cities such as Tulsa, Boston, and Kalamazoo (Bartik 2013;Bartik, Gormley, and Adelstein 2012;Hustedt, Barnett, and Jung 2008;Hustedt et al 2010;Weiland and Yoshikawa 2013;Wong et al 2008).…”
Section: State and Local Pre-k Programs: The Regression Discontinuitymentioning
confidence: 99%
See 2 more Smart Citations